2015
DOI: 10.5944/reop.vol.25.num.3.2014.13860
|View full text |Cite
|
Sign up to set email alerts
|

Enfoques de enseñanza de estudiantes en formación pedagógica. Un estudio exploratorio = Approaches to teaching of trainee teachers, an exploratory analysis

Abstract: Enfoques de enseñanza de estudiantes en formación pedagógica. Un estudio exploratorio Fuensanta Monroy et.al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
0
9
0
7
Order By: Relevance
“…Some possible explanations may be: a) the insufficient length of the intervention (one academic year) despite recommendations from some authors such as Postareff et al (2007); b) the fact that this particular training programme is a prerequisite for all those who wish to become a secondary teacher in Spain; many students enrol in this course in order to enhance their curriculum vitae in periods of economic crisis (Monroy et al, 2014), which in fact contrasts sharply with the intrinsic motivation of these would-be teachers found by Serrano and Pontes (2015); c) the fact that after the programme participants are aware of their weaknesses and inexperience, as well as the intrinsic difficulties in teaching, which may lead to a desire to keep some aspects under control such as what contents they teach, how they teach them, how they organise materials, etc. In sum, the findings from the qualitative analysis suggest that the initial teacher training programme did not yield the expected positive effect on participants, namely becoming more student-focused.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some possible explanations may be: a) the insufficient length of the intervention (one academic year) despite recommendations from some authors such as Postareff et al (2007); b) the fact that this particular training programme is a prerequisite for all those who wish to become a secondary teacher in Spain; many students enrol in this course in order to enhance their curriculum vitae in periods of economic crisis (Monroy et al, 2014), which in fact contrasts sharply with the intrinsic motivation of these would-be teachers found by Serrano and Pontes (2015); c) the fact that after the programme participants are aware of their weaknesses and inexperience, as well as the intrinsic difficulties in teaching, which may lead to a desire to keep some aspects under control such as what contents they teach, how they teach them, how they organise materials, etc. In sum, the findings from the qualitative analysis suggest that the initial teacher training programme did not yield the expected positive effect on participants, namely becoming more student-focused.…”
Section: Discussionmentioning
confidence: 99%
“…A paired-sample Wilcoxon signed-rank test was used in order to identify any changes in teaching approaches (quantitative data) after the intervention. Furthermore, the authors adapted a procedure previously used by Lindblom-Ylänne, Trigwell, Nevgi, and Ashwin (2006) and Monroy, Hernández Pina, and Martínez Clares (2014) that set a change variable that would allow to determine the shift/change in approach scores for individual participants when comparing pretest-posttest results. Five categories were developed which show the magnitude and direction of change (Table 2).…”
Section: Procedures and Data Analysismentioning
confidence: 99%
“…The link between approaches to teaching and approaches to learning is beyond their methodological origins as 'there is a relation between approaches to teaching and the quality of student learning outcomes' (Trigwell et al, 1999, p. 66). In addition, the relationship between surface approaches to learning and lower learning outcomes has been confirmed (e.g., Christie, 2015;Ramsden, 1992), while previous research has identified a direct association between teacher training courses and teachers' approaches to teaching (e.g., Gibbs & Coffey, 2004;Monroy et al, 2014).…”
Section: Approaches To Teaching and Pedagogical Implicationsmentioning
confidence: 83%
“…Por lo tanto, se puede afirmar que, el profesorado a través de sus métodos de enseñanza y estrategias tienen influencia en el aprendizaje del estudiante (Entwistle y McCune, 2004), y que los enfoques tienen importantes implicaciones en la educación, ya que el profesorado que recurre a un enfoque centrado en el alumnado tiene más probabilidad de hacer un aprendizaje de mayor calidad (Monroy, Hernández y Martínez, 2014).…”
Section: Estudios Efectuados Sobre Los Enfoques De Enseñanzaunclassified
“…A través del presente estudio, se pretende determinar en el contexto universitario y español, algunas de las variables que influyen al profesorado a la hora de emplear los enfoques de enseñanza, una vez que el EEES ya está implantado unos años. Entre las diferentes variables que pueden influir en la utilización de un determinado enfoque, se estudiará más detalladamente la formación del profesorado, pues, como afirmaron Monroy et al (2014), conocer el impacto de la formación sobre los enfoques de enseñanza es vital para la mejora del sistema educativo, en vista de la influencia de éstos en los resultados de aprendizaje de los estudiantes.…”
Section: Estudios Efectuados Sobre Los Enfoques De Enseñanzaunclassified